Organ sparing for rectum and quality of surgery for preventing local recurrences - Temple, Walley J. (Radiology and oncology (Ljubljana), 2000)
The progress in the management of rectal cancer in the last 100 years has beenphenomenal. From the days of Myles abdominal perineal resection at the beginning of the 20th century we have progressed to being able to manage most rectal cancers without the need for a permanent colostomy and from a surgical procedure associated with 40% local recurrence to one with less than 5%. Adjuvant modalities with radiotherapy and chemotherapy have similarly proven useful in advanced disease to improve not only local control but also survival. In the manuscript the particular attention is paid to two aspeets: 1) the surgical technique that is so critical in improving survival by improved local control and 2) looking at anal-preserving surgeries for advanced and low rectal cancers. It is concluded that a properly done procedure using the TME appronch supported by preop radiation for advanced lesions will result in excellent local control and function in over 90% of lowrectal cancers.
Keywords: kirurško zdravljenje; Neoplasm recurrence, local; Neoplasm staging; Prevention and control; rak (medicina); Rectal neoplasms; rektum; Surgery